Study on New Principles of Treatments in Malignant Hematological Diseases, as Acute and Chronic Lymphocytic Leukemia or Multiple Myeloma - Aurelian Udristoiu (New Frontiers in Medicine and Medical Research Vol. 3, 2021)
B-cell chronic lymphocytic leukemia (B-CLL) is one of the most common hematologic malignant diseases which had especially to the elderly. It is particularly interesting that, although known as apathologicalentity and studied for decades. Aim of this study is to present the latest researches in the field of molecular medicine, in terms of treatments in malignant hemopathies, emerged from the P53 gene deletion in human lymphoma genome. Method: In recent years proved that the best techniques in the investigation of malignant lymphocytes are the Flow Cytometry, Elisa, ICT and Fluorescence in Situ Hybridization (FISH). This method is used as an alternative to chromosomal banding, a conventional application in molecular medicine. Discussion: Recent, endogenous somatic gene therapy research is a basic of trial clinical and therapeutic trial. The DNA is used to treat a disease arising as a result of mutations in chromosomal regions. In the past few years, this method has been included in the treatment of CLL, acute lymphocytic leukemia, [ALL], or multiple myeloma [MM]. Conclusion: The frequencies of P53 gene mutations and deletion in CLL can be categorized as individual biomarkers in proteomic and genomic profile for this type of leukemia that can be implemented in targeted patient treatment of personalized medicine.